Automated off-line programming for Rapid Prototyping using Gas Metal Arc Welding - Ribeiro, A. F. M. (Cranfield University, 1995)
Rapid Prototyping is a recent CAD/CAM based manufacturing technique which produces prototypes of components in a fraction of the time normally required. This technique normally involves drawing the part as a 3 Dimensional solid model using a CAD program and then 'printing' it in 3 Dimensions. The raw material can be a photopolymer or thermoplastic which solidifies when in contact with light. Other materials are available although producing the final parts a 100% metal is not very usual. Some disadvantages of these techniques are: a) 100% metal prototypes cannot normally be made directly. b) only prototypes can be produced instead of the final component. c) machine size limits the size of the final component. d) very thin layers are deposited. This makes the build up more time consuming and mostly suitable to small components. The main objective of this work was to overcome these disadvantages by creating a new Rapid Prototyping technique using Robot Fusion Welding. In the pre-production phase, it is important to make a prototype not only for visualisation but also to test and assess it in its real function. Therefore, prototyping in resin a component which is going to be made in metal has no use for assessing purposes. This technique, besides making the prototype in metal can also be used as a production technique to make the real usable final component. It even allows the use of different metals along its structure in the welding filler wire is changed. This makes it possible to have different structural characteristics in the same component a required. None of the slicing algorithms developed for other Rapid Prototyping processes were applicable to this new technique and therefore a new slicing concept (and routine) was created specifically. I addition, an interface for off-line programming and quality documentation was evolved. The technique developed has been tested by fabricating several 'test' components and both the dimensional accuracy and component integrity have been evaluated and proved to be successful.